Integrated risk management: A conceptual framework with research overview and applications in practice - KOUVELIS, Panos (Institutional Knowledge at Singapore Management University, 2011)
This chapter presents an action‐based supply chain risk management framework that has emerged from industry practice and academic research. For practitioners, this conceptual framework can serve as a guideline to devise risk management strategies that suit their specific supply chain environments. For academicians, one can map the research in the growing field of integrated risk management research within the context of this framework, and identify potentially fruitful directions for future research. The framework of supply chain risk management proposes a two‐stage action plan: a planning stage and an execution stage. Risk mitigation strategy has been the main focus of the supply chain risk management research. The chapter discusses the landscape of the current academic research in this area. The growing research of supply chain risk management can be largely divided into three themes: managing risk through operational strategies, integrated operations finance risk management, and supply chain finance.